ASEAN’s centrality in a rising Asia - Ho, Benjamin (2016)
The S. Rajaratnam School of International Studies (RSIS) was established in January 2007 as an autonomous School within the Nanyang Technological University. Known earlier as the Institute of Defence and Strategic Studies when it was established in July 1996, RSIS’ mission is to be a leading research and graduate teaching institution in strategic and international affairs in the Asia Pacific. To accomplish this mission, it will: • Provide a rigorous professional graduate education with a strong practical emphasis, • Conduct policy-relevant research in defence, national security, international relations, strategic studies and diplomacy, • Foster a global network of like-minded professional schools.